Anaemia- related knowledge amongst pregnant women in Kuala Terengganu - Hasnah, Zani; Hassan Basri, Mukhali; Mohd Razif, Shahril (Penerbit Universiti Sultan Zainal Abidin, 2020)
The prevalence of anaemia amongst pregnant women in developing countries is increasing yearly, particularly in Malaysia. This problem may be due to their lack of knowledge of anaemia and food choice. This study aimed to measure the knowledge levels on anaemia and iron absorption amongst pregnant women in Kuala Terengganu, as well as the association of knowledge levels between socio-demographic characteristics. Pregnant women were selected from government health clinics located in Kuala Terengganu, Malaysia. A total of 71 pregnant women aged between 18 and 44 years participated in the study. They self-administered the socio-demographic form and the knowledge questionnaire. Overall, they had moderate knowledge level with mean score of 57.41 ± 4.80. A significant association was found between knowledge level and monthly household income (p<0.05). Meanwhile, no significant association was found between knowledge level with socio-demographic characteristics (age, gravida, occupation, husband’s occupation, and education level) (p>0.05). This study provided an early insight into knowledge of anaemia amongst pregnant women in Kuala Terengganu. Educational intervention should be implemented to increase and improve pregnant women’s knowledge of anaemia and iron absorption.